2019
DOI: 10.5751/ace-01397-140208
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring boreal avian populations: how can we estimate trends and trajectories from noisy data?

Abstract: Avian Conservation and Ecology 14(2): 8 http://www.ace-eco.org/vol14/iss2/art8/ à différents stades de leur cycle de vie annuel. Ces facteurs sont souvent structurés de manière hiérarchique et peuvent influencer les populations aux niveaux local, régional ou continental. Certains des défis associés à la délimitation des populations et l'identification des facteurs qui influencent les populations peuvent être traités à l'aide de la multitude de méthodes d'échantillonnage et d'analyse disponibles pour examiner l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 194 publications
0
17
0
Order By: Relevance
“…Other programs collect effort data that can be used to analytically control for variation, such as National Audubon Society’s Christmas Bird Count (Soykan et al 2016) and eBird (Hochachka et al 2012). However, few community science programs collect the ancillary data (e.g., distance, time of first detection) or utilize the structured protocols (e.g., repeat surveys, double observers) needed to produce accurate occupancy or abundance estimates corrected for imperfect detection (Roy et al 2019). Climate Watch was designed as a structured community science program, which uses spatially repeated surveys within predefined grid cells to enable estimates of detection probability and, consequently, occupancy probability.…”
Section: Introductionmentioning
confidence: 99%
“…Other programs collect effort data that can be used to analytically control for variation, such as National Audubon Society’s Christmas Bird Count (Soykan et al 2016) and eBird (Hochachka et al 2012). However, few community science programs collect the ancillary data (e.g., distance, time of first detection) or utilize the structured protocols (e.g., repeat surveys, double observers) needed to produce accurate occupancy or abundance estimates corrected for imperfect detection (Roy et al 2019). Climate Watch was designed as a structured community science program, which uses spatially repeated surveys within predefined grid cells to enable estimates of detection probability and, consequently, occupancy probability.…”
Section: Introductionmentioning
confidence: 99%
“…When that assumption is violated, however, inference is compromised. Without identifying the relative contributions of each process affecting the index value, the potential effectiveness of management actions can be limited (Roy et al 2019). For example, declines in abundance caused by human factors (e.g., overharvest, disturbance) may be masked in an index if temporary immigration increases in the area covered by the index (i.e., possible source-sink dynamics).…”
Section: Discussionmentioning
confidence: 99%
“…Our results expand on previous analysis of black and surf scoters by Reed et al (2017), which also identified the Barrenlands as an area of high multi-species importance. The areas identified by our models as being of highest multi-species importance, including the Barrenlands and parts of northern Quebec, fall outside the boundaries of most North American breeding bird surveys including the Waterfowl Breeding and Population Habitat Survey (Roy et al 2019); however, the Barrenlands are currently being targeted for additional pilot surveys to quantify the extent of use by nesting sea ducks (Reed et al 2017). In our analysis, no sites were in the top 10% of suitable breeding habitats for all species.…”
Section: Discussionmentioning
confidence: 99%